Геоэкологическое состояние бассейна реки Стырь в Волынской области - Нетробчук, Ірина Марківна; Netrobchuk, Iryna M. (Могилевский областной отдел Белорусского географического общества, 2014)
Geoecological state of grainage-basin system river Styr is considering in the article by using criterious of anthropogenic loading. They are: use of landed reserves, quality of water and soils, the state of water scoops. The spectrum of correlations of system ‘population-environment’ was formed in the drainagebasin river Styr. The spectrum dеtermined it’s modern ecological condition. Anthropogenic loading on the drainage-basin was fixed by using types of activities. They are: agricultural use of lands, industry, transport, recreation and measures of nature protection activity.

Аналізуецца геаэкалагічны стан басейну р. Стыр з выкарыстаннем крытэрыяў антрапагеннай нагрузкі (выка- рыстання зямельных рэсурсаў, якасці вады, глебы, стану водазабораў). У басейне р. Стыр склаўся ўвесь спектр узаемасувязяў сістэмы насельніцтва-прырода, які вызначае яго сучасны экалагічны стан. Антрапагенная нагрузка на басейн прааналізавана па відах дзейнасці: насельніцтва, меліярацыйныя работы, сельскагаспадарчае выкарыстанне зямель, прамысловасць, транспарт, рэ- крэацыя і прыродаахоўная дзейнасць.
Geoecological state of grainage-basin system river Styr in Volyn region
Keywords: басейн річки; антропогенне навантаження; геоекологічний аналіз